Strategies for Teaching Academic Vocabulary: Strategies for Teaching Academic Vocabulary - Xoliqov, Farxod (Maktabgacha taʼlim jurnali, 2021)
Nowadays teaching is a crucial part of teaching foreign languages so that a number of teachers use variety effective strategies to teach several types of vocabulary as we have discussed in our first chapter in different ways.